A Bear-Y Good Neighbor - Kathleen Weidner Zoehfeld (United States RANDOM HOUSE DISNEY, 2001)
Pooh sets out to do a neighborly deed by bringing a present to Piglet, but on his way he learns a lot of things about his community as he meets people, sees new things, and travels new paths.
Keywords: Winnie The Pooh -- Winnie The Pooh